Synthesis, Characterization of Some Novel 1, 4- Benzoxazine- 3- One Derivatives Starting From O-Amino Phenol and Study Their Biological Activity - Helen Abd Al Hassan Mahmood (Journal of Global Pharma Technology, 2020)
In this work: Benzoxazinone derivatives were used as a precursor to synthesize of many heterocyclic systems. The aim of current study was to use the easily available o-amino phenol for the synthesize of 1, 4-benzoxazine-3-one. The benzoxazinone compound of interest was synthesized by reacting the o-amino phenol with chloroacetyl chloride, The treatment of o-chloro acetamidophenol (FH) and anhydrous potassium carbonate in refluxing DMF afforded the corresponding 1,4-benzoxazine -3-one (1) in excellent yield. The treatment of ethyl chloroacetate with compound (1) gave compound (2), while compound (3) was produced by reacting of hydrazine hydrate with compound (2). Compound (3) was used as precursor to synthesize (5a-d),(ST),(6),(7a,7b),(8,9) by its reaction with different chemical reagents, while on treatment of the compound (1) with 4-nitrobenzaldehyde in acetic anhydride: triethylamine (2:1) as a solvent gave chalcone (10). The structures the synthesized compounds have been confirmed by FT-IR, 1H-NMR, and Mass spectroscopy. The synthesized derivatives have been screened in vitro for antimicrobial properties. The results of this investigation revealed that the newly synthesized compounds are potent antimicrobial agents.Keywords: 2-Aminophenol, Benzoxazinone, Schiff’s base, 1, 2, 4-triazole, Antimicrobial.